Preparation and properties of MoS2 modified polydimethylsiloxane/monomer casting nylon - Jinfei Shangguan; Ling Song; Feng Lang; Haiyang Yang; Duxin Li; Jin Wang; Qibin Jiang; Yilan You (Materials Research Express, 2021)
MoS _2 reinforced PDMS/MC nylon composites had been fabricated by in situ polymerization to further enhance the comprehensive properties of nylon material. Polydimethylsiloxane was pre-sythesized as the activator of the system and MoS _2 was compounded as the wear-resisting agent. The thermal stability, mechanical properties, friction and wear properties of composites with different MoS _2 contents were tested. The results showed that the crystallization and thermal stability of nylon matrix were increased with the addition of MoS _2 , while the tensile strength and impact strength were slightly reduced. The composites finally presented excellent friction properties with 3 wt% MoS _2 , whose friction coefficient was reduced to 0.75 (18.48% decrease) corresponding to the wear rate of 0.4145 × 10 ^−8 g Nm ^−1 .